2009
DOI: 10.1016/j.socscimed.2008.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the extent of inequalities in health across urban and rural areas: Evidence from a national sample in England

Abstract: Studies of inequalities in health between rural and urban settings have produced mixed and sometimes conflicting results, depending on the national setting of the study, the level of geographic detail used to define rural areas and the health indicators studied. By focusing on morbidity data from a national sample of individuals, this study aims to examine the extent of inequalities in health between urban and rural areas, as well as inequalities in health across rural areas of England. Multilevel analyses for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 42 publications
(63 reference statements)
3
77
1
4
Order By: Relevance
“…To our point of view, in past population, we should take into account the global lifestyle rather than searching to define a clear socioeconomic status. Besides we found in our last studies clear differences between rural and urban lifestyle, what was confirmed by many studies (Betsinger, 2007;Budnik & Liczbinska, 2006;Riva et al, 2009;Van de Poel et al, 2007;Williams & Galley, 1995). We also must take in mind that in past population, we must deal with the "osteological paradox" (Byers, 1994;Wood et al, 1992;Wright & Yoder, 2003).…”
Section: Have You Spoken Of a Possible Socioeconomic Influence On Densupporting
confidence: 79%
“…To our point of view, in past population, we should take into account the global lifestyle rather than searching to define a clear socioeconomic status. Besides we found in our last studies clear differences between rural and urban lifestyle, what was confirmed by many studies (Betsinger, 2007;Budnik & Liczbinska, 2006;Riva et al, 2009;Van de Poel et al, 2007;Williams & Galley, 1995). We also must take in mind that in past population, we must deal with the "osteological paradox" (Byers, 1994;Wood et al, 1992;Wright & Yoder, 2003).…”
Section: Have You Spoken Of a Possible Socioeconomic Influence On Densupporting
confidence: 79%
“…These linkages are better established for deprivation (Williams, 2003;Jama andDugdale, 2012: Marmot et al, 2010). Evidence on associations with regard to rurality is more mixed (Riva et al, 2009). Smith et al (2008), in an international comparative review, note that rurality can link to access to and provision of health services but may not confer health disadvantage, while Midouhas and Flouri (2013) suggest that UK children do not vary in numeracy skills with respect to urban or rural residence but reading age tends to be higher in major urban areas.…”
Section: Our Key Exposure Variables Were Literacy and Numeracy Test Rmentioning
confidence: 99%
“…Geographic inequalities in health are regularly found in the UK (Thomas et al, 2010;Norman et al, 2011), with different levels of mortality and self-reported health found in rural and urban areas (Levin and Leyland, 2005;Levin, 2003;Riva et al, 2009;Riva et al, 2011) and in deprived and more affluent areas (Rees et al, 2003;Shaw et al, 2004;Norman et al, 2005;Romeri et al, 2006). Whilst levels of infant mortality are steadily reducing in England and Wales, gradients across differently deprived areas largely persist (Norman et al, 2008).…”
Section: Prevalence Of Life-limiting and Life-threatening Illness In mentioning
confidence: 99%